Challenges of Rabies Surveillance in the Eastern Amazon: The Need of a One Health Approach to Predict Rabies Spillover - Bastos, Victor; Mota, Roberta; Guimarães, Mylenna; Richard, Yuri; Lima, André Luis; Casseb, Alexandre; Barata, Gyovanna Corrêa; Andrade, Jorge; Casseb, Livia Medeiros Neves (Frontiers in Public Health, 2021)
Brazil has been promoting essential improvements in health indicators by implementing free-access health programs, which successfully reduced the prevalence of neglected zoonosis in urban areas, such as rabies. Despite constant efforts from the authorities to monitor and control the disease, sylvatic rabies is a current issue in Amazon's communities. The inequalities among Amazon areas challenge the expansion of high-tech services and limit the implementation of active laboratory surveillance to effectively avoid outbreaks in human and non-human hosts, which also reproduces a panorama of vulnerability in risk communities. Because rabies is a preventable disease, the prevalence in the particular context of the Amazon area highlights the failure of surveillance strategies to predict spillovers and indicates the need to adapt the public policies to a “One Health” approach. Therefore, this work assesses the distribution of free care resources and facilities among Pará's regions in the oriental Amazon; and discusses the challenges of implanting One Health in the particular context of the territory. We indicate a much-needed strengthening of the sylvatic and urban surveillance networks to achieve the “Zero by 30” goal, which is inextricable from multilateral efforts to combat the progressive biome's degradation.